2023
DOI: 10.1021/jasms.3c00019
|View full text |Cite
|
Sign up to set email alerts
|

Practical Semiquantification Strategy for Estimating Suspect Per- and Polyfluoroalkyl Substance (PFAS) Concentrations

Abstract: Semiquantitation of suspect per-and polyfluoroalkyl substances (PFAS) in complex mixtures is challenging due to the increasing number of suspect PFAS. Traditional 1:1 matching strategies require selecting calibrants (target−surrogate standard pairs) based on head group, fluorinated chain length, and retention time, which is time-consuming and requires expert knowledge. Lack of uniformity in calibrant selection for estimating suspect concentrations among different laboratories makes comparing reported suspect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Thirty-four of the 50 target PFASs were quantified above the LOQ in at least one of the 92 samples. A total of 188 suspect PFASs from the NIST list were identified with a confidence of Level 4 or higher and semi-quantified in at least one of the 92 samples. PFAS occurrence and concentration data from AFFF-GW, LL, BL, and WWTP samples have been previously reported from sites around the world.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-four of the 50 target PFASs were quantified above the LOQ in at least one of the 92 samples. A total of 188 suspect PFASs from the NIST list were identified with a confidence of Level 4 or higher and semi-quantified in at least one of the 92 samples. PFAS occurrence and concentration data from AFFF-GW, LL, BL, and WWTP samples have been previously reported from sites around the world.…”
Section: Resultsmentioning
confidence: 99%
“…Details on assigning confidence to suspect matching is provided in the Supporting Information . Suspect concentrations were estimated using an average PFAS calibration curve constructed from the area of target PFASs divided by the average area of the 22 surrogate areas versus target concentration in units of nmoles/L . Suspect concentrations were reported in ng/L after converting from nmoles/L using the suspect molar mass.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To simplify this process, surrogates are often used but there is a lack of uniformity in calibrant selection for estimating suspect concentrations among different laboratories, making comparison of reported suspect concentrations dif icult. In this context, Cao et al (2023) recently proposed a practical approach in which the area counts for 50 anionic and 5 zwitterionic/ cationic target PFAS were ratioed to the average area of their respective stable-isotope labelled surrogates to create "average PFAS calibration curves" for suspects detected in both negative-and positive-electrospray ionization modes. The method was developed on a LC-Q-ToF instrument using data-independent acquisition and applied to a well characterized aqueous ilm forming foam standard sample.…”
Section: Semi-quanti Ication Strategy For Estimating Suspect Pfas Con...mentioning
confidence: 99%
“…Chromatography, high-resolution and tandem MS, and Kendrick Mass Defect (KMD) analysis are among tools that are widely used. 14,24,25 In recent years, ion mobility spectrometry (IMS) has shown unique strength in the analysis of halogenated xenobiotics, including PFAS, due to its capability in separating ions by size, shape and charge state in the gas phase. 26−29 By coupling drift-time ion mobility spectrometry (DTIMS) to LC-MS, Foster et al demonstrated a unique trendline of collision cross section vs m/z for halogenated xenobiotics compared to biological molecules, facilitating the identification of xenobiotics in a complex sample matrix.…”
Section: Introductionmentioning
confidence: 99%